Total mercury in marine species from the French coast of the Eastern English Channel. Issue 4 (21st April 2017) - Henry, Françoise; Mahfouz, Céline; Delegrange, Alice; Courcot, Lucie
ABSTRACT: Mercury (Hg) in fish can present a potential risk to wildlife and human consumers. Mercury levels were determined in 12 fish species and 2 invertebrate species from the French coast of the Eastern English Channel collected in June and November 2012. Total mercury concentrations in the muscle tissues ranged between 0.04 and 1.63 µg g -1 (d.w.). Dab and sandeel displayed a significant positive correlation between Hg concentrations and fish length. Seasonal differences in Hg concentrations were observed for dab and shrimp. The lesser weever showed significantly higher concentrations of Hg (0.97 ± 0.34 µg g -1 d. w.) than all other species. Gobies and sprat, which had the smallest size, showed significantly lower concentrations than herring, whiting, pout and sardine. Among the considered species, flatfish such as dab, flounder, plaice and sole displayed intermediate levels of Hg. In the present study, the fish age expressed as specimen length seems to be one of the major factors governing Hg contents in muscle tissues. Finally, mercury concentrations in commercial fish from the Eastern English Channel were below the levels fixed by the European Union for total mercury in edible parts of fish products.